Ad Hoc Networks 5th International ICST Conference, ADHOCNETS 2013, Barcelona, Spain, October 2013, Revised Selected Papers - Sherif, Mostafa Hashem; Mellouk, Abdelhamid; Li, Jun; Bellavista, Paolo (Lecture Notes of the Institute for Computer Sciences, Social Informatics and Telecommunications Engineering, 2014)
This book constitutes the thoroughly refereed proceedings of the 5th International Conference on Ad Hoc Networks, ADHOCNETS 2013, held in Paris, Barcelona, Spain, in October 2013. The 14 revised full papers presented were carefully selected and reviewed from numerous submissions. The papers cover a wide range of applications, commercial and military, such as mobile ad hoc networks, sensor networks, vehicular networks, underwater networks, underground networks, personal area networks, home networks, and large-scale metropolitan networks for smart cities. They are organized in topical sections on Wireless Sensor Networks, Routing, Applications, and Security.